Model Pembelajaran Bersanad sebagai Strategi Peningkatan Pengetahuan di Pesantren - Mita Nur Khasanah; Akbar Yusgiantara; Rustam Ibrahim (ANWARUL, 2025)
Research on pesantren education has increasingly emphasized the importance of traditional learning methods, yet studies that specifically examine the role of sanad as an epistemological and pedagogical framework within modern educational models remain scarce. This study aims to investigate the function of sanad-based education in maintaining the authoritative transmission of knowledge and shaping the academic and moral character of santri in pesantren. A qualitative methodology with a descriptive-analytical framework is employed, involving selected expert educators and academic documents obtained through purposive sampling. Data were collected using document analysis sheets and semi-structured interviews, then analyzed thematically to identify patterns of knowledge transmission, character formation, and curriculum integration. The findings show that sanad functions as a fundamental mechanism that guarantees the authenticity of knowledge, reinforces teacher authority, and facilitates the internalization of moral and intellectual norms. These results advance the theoretical framework of Islamic epistemology and deepen understanding of the role of pesantren in preserving legitimate and ethical knowledge networks in the digital era. The study also affirms that preserving sanad is crucial for upholding academic integrity and character education in pesantren, and recommends that educational institutions and policymakers support the revitalization of sanad-based pedagogy. This research is significant for the theoretical advancement of Islamic education studies and offers practical recommendations for curriculum development in Islamic educational institutions, while underscoring future research prospects on integrating sanad with digital education and pedagogical innovations.